Jetzt ist die Zeit für verstärkten öff entlichen Wohnungsbau - Sebastian Dullien; Carolin Martin (Wirtschaftsdienst, 2023)
– The German construction industry is facing major challenges. Rising interest rates, high material costs and high energy prices have led to a sharp drop in orders and declining building permits. Consequently, capacity utilisation in the construction industry will fall while the shortage of aff ordable housing increases. This article proposes appropriate instruments for increased public housing construction. We recommend that the federal government supports the federal states and municipalities in the areas of planning, fi nancing and controlling and increases and expands KfW-programmes.
Keywords: R31; R38; 330; Soziale Wohnungspolitik; Wohnungsbau; Deutschland